The protective strategy of antioxidant enzymes against hydrogen peroxide in honey bee, Apis mellifera during two different seasons - Ahmad M. Korayem (Journal of Biology and Earth Sciences, 2012)
Introduction: Honey bees collect floral nectar and pollens, for feeding, which rich with allelochemicals and phenols. The oxidation of these materials produce reactive oxygen species (ROS), among them the hydrogen peroxide (H2O2) and superoxide. The honey bee antioxidant enzymes are of particular interest in detoxification of these ROS. Superoxide dismutases (SODs) are the first line of defense against oxygen free radicals. In concert with catalase; SODs have strong antioxidant properties. Since catalase is inefficient at removing H2O2 because of its high Km the ascorbate peroxidase (APOX) serves better in H2O2 detoxification.Results: The antioxidant enzymes under investigation showed highly significant variation during the whole duration of the experiment. However, a combined effect of months, race (Hybrid and Carniolan) and type (foraging and nursing) showed similar activity in SOD and CAT.Conclusion: The correlations between SOD, CAT and APOX, indicating that there must be a specific manner strategy for managing peroxides at safe levels. The increase or decreases of the antioxidants are according to the contents and levels of peroxides.